(untitled) (Revista Archai, 2018)
This article aims to investigate the assumptions that lead to a conviction by moral philosophy of the various practices of deceit commonly involved under the name of hypocrisy. The argument is developed around three questions: first, on the assumptions under which the various practices and strategies of deceit ”“ such as: simulation, dissimulation and irony ”“ become a problem to moral philosophy. Secondly, in order to understand how the hypocrisy, originally assigned to the art of the actor, comes to be part of the moral sphere designating, as art of deception, the set of those morally reprehensible strategies. Finally, how could be set a way opposed to this conviction. As I argue, that would happen with a double presumption: a distinction of perspectives between deceiving and being deceived ”“ with their respective modes of evaluation ”“ and through a re-evaluation of thought forms linked to astute intelligence that the Greeks called metis. Under these assumptions, hypocrisy could be linked to the ethical-poietical agenda of the creation of self.